Trends and disparities in stroke mortality with diabetes as a contributing cause among U.S. adults, 1999–2023: a uniform-definition national analysis of long-term decline and a post-2014, pandemic-era increase - Yan Cheng; Ji Li; Yunzhou Yang (BMC Public Health, 2026)
Abstract Background Diabetes mellitus is a major contributor to cerebrovascular risk and stroke-related mortality. Although U.S. cardiovascular mortality declined for decades, national estimates for stroke mortality among people with diabetes have been inconsistent, partly because of differences in case definition and in the handling of the 2018 change in population race classification. Methods Using the CDC WONDER Multiple Cause of Death database, we studied U.S. adults aged ≥ 25 years (1999–2023) under a single, frozen case definition: stroke as the underlying cause (ICD-10 I60–I69) with diabetes mellitus (E10–E14) contributing. Age-adjusted mortality rates (AAMRs; 2000 U.S. standard) were analysed with segmented log-linear regression. Sensitivity analyses excluded the 2020–2021 pandemic peak, tested a 2020 level shift, applied inverse-variance weighting and age-specific count models, denominated the rate by NHANES diabetes prevalence, and examined proportional mortality; subgroup change points were bootstrapped. Results Among 298,908 stroke deaths with contributing diabetes, the national AAMR declined from 1999 to 2014 (APC − 3.97%; 95% CI − 4.38 to − 3.56) and then rose through 2023 (+ 3.19%; +2.40 to + 3.99), from 4.28 to 5.37 per 100,000. The increase was concentrated in the pandemic era: the strictly pre-pandemic segment (2014–2019) was not significant (+ 0.55%, P = 0.31; +0.73% in an age-specific count model), a 2020 level shift fit best, and the rise persisted after excluding 2020–2021 (+ 2.88%). It was not accounted for by rising diabetes prevalence (rate per adult with diabetes + 2.92%; age-adjusted prevalence flat), although increasing diabetes ascertainment on death certificates could not be excluded. The non-Hispanic Black: White rate ratio was roughly stable (≈ 2.0), while the absolute gap re-widened (9.37 vs. 4.71 per 100,000 in 2023). The increase was broad but heterogeneous, with the largest point estimate in the South and no increase in the Northeast. Conclusions After a long decline, stroke mortality among adults with diabetes stopped falling around 2014 and increased modestly in the pandemic era. This increase was not accounted for by rising diabetes prevalence, although increasing diabetes ascertainment could not be excluded, and the rate remained above the 2014 nadir. These findings underscore continued surveillance and life-course prevention, with the greatest burden among non-Hispanic Black adults and in the South.